Republicanismo inglês e a concepção neorromana de liberdade: a problemática interpretação de Quentin Skinner - Barros, Alberto Ribeiro Gonçalves de (Discurso, 2022)
The aim of the article is to discuss Quentin Skinner’s interpretation of the conception of freedom found in English authors who defended the republican regime established in England between 1649 and 1660. In his historical narrative, this conception of freedom, characterized by the absence of arbitrary interference, would be inspired by the Roman theory of free States, expressed mainly in the republican thought of Machiavelli, which would characterize English republicanism as a Machiavellian moment. The intention is to show that this narrative is problematic: first, because it is not possible to extract from Machiavelli’s analyzed texts this conception of freedom; later, if these English authors used Machiavelli’s arguments in favor of the republican regime, they did not accept its main foundations.